WANPRETASI PELAKU USAHA TERHADAP KONSUMEN DALAM TRANSAKSI JUAL BELI MELALUI ELEKTRONIK : STUDI KASUS PT. GRAB TOKO INDONESIA - Reyhan Zaki Saputra (2023)
Default in general is a right and obligation that arises from an agreement that is indeed influenced by good parties related to business actors and consumers. In this case the business actor defaulted on his consumer, however, the business actor did not carry out the compensation process that he should have done. Business actors, in this case, are the owners of PT Grab Toko Indonesia, offering a practical buying and selling process with e-commerce, the seller also provides a large discount and is very attractive to many groups, giving rise to many benefits for business actors. However, the seller does not fulfill his promise to deliver and deliver the goods that have been purchased and fulfill the obligations for the consumer, so that in the process a default occurs. Unfortunately, in conditions related to the court decision, this did not provide a form of compensation to the victim, where the victim was deceived and compensation was never given. So that this is what then causes the victim to fight for legal action in the form of a request for compensation, as the author has explained. The research method used in this research is normative research which is carried out by reviewing and analyzing library materials in the form of legal book literature. In this case the author uses 2 theories, namely the theory of legal protection and the theory of legal responsibility, besides that the author also provides an explanation that liability for compensation in cases of default is a right that must be received by the victim and also an obligation that must be carried out by the perpetrator.